A rare case of isolated mitral valve endocarditis by Gemella sanguinis: Case report and review of the literature. (2020) - Sideris, Antonios C.; Zimmermann, Eric; Ogami, Takuya; Avgerinos, Dimitrios V.
Highlights: Gemella sanguinis is a very rare cause of infective endocarditis. Only 12 cases previously reported in the literature, only two of which involved exclusively the mitral valve. Usually associated with preexisting cardiac condition or oral infection/instrumentation. Valve replacement along with prolonged antibiotic course resulted in successful outcomes in the majority of cases. Abstract: Introduction: Gemella sanguinis is an extremely rare cause of infectious endocarditis, with only 12 cases previously reported in the literature. Here we report the third known case of isolated mitral valve endocarditis secondary to G. sanguinis . Presentation of case: A 53-year-old man with mitral valve prolapse and history of recent dental instrumentation presented with malaise, thigh and finger pain and new pansystolic murmur. He was diagnosed with severe mitral insufficiency due to infectious endocarditis secondary to G. sanguinis . He underwent mitral valve replacement and was treated with a long course of antibiotics. Discussion: G. sanguinis is a rare cause of infectious endocarditis with very few reported cases in the literature. In the majority of reported cases, a strategy of valve replacement along with prolonged antibiotic course results in good outcome for the patient.